Pain and Depression Symptoms During the Third Trimester of Pregnancy. Issue 6 (November 2020) - Vignato, Julie; Perkhounkova, Yelena; McCarthy, Ann Marie; Segre, Lisa S.
Abstract: Purpose: To assess the association between depression symptoms and pain characteristics, including pain intensity, location, and effectiveness of pain management strategies, among women in their third trimester of pregnancy. Design: Descriptive, exploratory cross-sectional study. Setting: Mobile health pregnancy application (app). Participants: A convenience sample of women in their third trimester of pregnancy from across the United States. Methods: Women completed demographic questionnaires, the Brief Pain Inventory, and Edinburgh Postnatal Depression Scale (EPDS) through an online Web site. Results: N = 132 women participated. The sample was demographically diverse. . Women ranged in age from 18 to 39 years (M 28.1 ± SD 5.2). Most women were Caucasian (68%), with smaller percentages of Hispanic (12%) and African American (11%) women. Most had commercial insurance (59%) and a partner (85%). Of the 132 women, 79.6% reported moderate-to-severe pain. Approximately 93% experienced back and pelvic pain, whereas 27% experienced moderate-to-severe depression symptoms. Bivariate and linear regression analyses revealed that higher EPDS depression scores were associated with higher levels of pain ( p < .01). Other variables significantly associated with higher EPDS scores were White race ( p = .04), marital status ( p = .05), and headache ( p < .01). Clinical Implications: In the third trimester of pregnancy, pain affects more than two-thirds of women and may occur with and without depression symptoms. Although the value of universal depression screening during pregnancy is widely recognized, our findings suggest clinical outcomes for pregnant women would improve with a standardized, multidimensional screen for both pain and depression symptoms. Nurses are ideally positioned to assess and advocate for the combined treatment of pain and depression. Abstract : In the third trimester of pregnancy, pain affects more than two-thirds of women and may occur with and without depression symptoms. In this study, 132 women during third trimester pregnancy responded to questions about pain and depressive symptoms, Although the value of universal depression screening during pregnancy is widely recognized, findings suggest clinical outcomes for pregnant women would improve with a standardized, multi-dimensional screen for both pain and depression symptoms. Nurses are in an ideal position to assess and advocate for the combined treatment of pain and depression.